Comparative potential of biogas production from the distillery, fruit and vegetable waste and their mixtures (digestion) - Gebresilasie Gebremedhin Gebresilasie; Mulualem G. Gebreslassie; Mebrahtom Gebresemati (Heliyon)
Biogas is becoming increasingly important as a renewable energy source in the face of global warming and declining fossil fuel reserves. Biogas is produced by anaerobic digestion of organic materials which can be available from various wastes such as agro-industrial, human, fruit waste, distillery, animal waste and aquatic plants. This study deals particularly with the comparative potential of biogas production from distillery, fruit and vegetable waste and their mixtures (digestion). The materials used as feed in this research were distillery waste which is dark-colored liquid waste from Desta Alcohol and Liquor Factory Private Limited Company. Fruit and vegetable waste such as banana peels, papaya, mango, tomato, avocado, cabbage leaves, watermelon skin, and orange skin were collected from juice houses and fruit and vegetable wholesale markets in Mekelle City, and Cow manure used as a buffer solution, collected from Desta Alcohol and Liquor Factory PLC. Waste samples were characterized for total solids, volatile solids, pH, biochemical oxygen demand, and chemical oxygen demand according to established standards. Biogas was analyzed using a biogas analyzer, an ORSAT apparatus for CO2, and a TUTWILER apparatus for H2S. Finally, the %CH4 was calculated from 100 % by ignoring other gases. The maximum biogas production from all wastes was observed at 37 °C. Mixture (co-digestion) produced high biogas in litter (L): 6.95, 9.47 and 9.54 at 20 °C, 37 °C and 50 °C respectively. The maximum methane composition was observed from the co-digestion (M) in (%) 67, 70 and 70.3 at 20 °C, 37 °C and 50 °C respectively. Methane yield was calculated at both temperature and substrates (waste). Comparatively, maximum methane yield was observed at 37 °C for distillery waste, fruit vegetable waste and mixture(digestion); 0.032, 0.061 and 0.079 L per gram volatile solids digestion (LCH4/gVS) respectively.